Localising Global Norms : The Role of Cities in Advancing the Net-Zero Agenda - Adamovská, Nikola; Veselý, Zdeněk, 1950-; Peterková, Jana, 1971-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This dissertation investigates how cities engage with the net-zero norm in global climate governance. It addresses three questions: (1) What factors influence city participation in the UNFCCC’s Race to Zero campaign? (2) How does the net-zero norm diffuse across cities, and what role do national governments play in this process? (3) To what extent are net-zero commitments institutionalised within municipal governance? A mixed-methods design combines probit regression analysis of city participation with qualitative case studies of ten cities across different regime types, governance systems, and regional contexts. The findings show that regime type and national government alignment are stronger predictors of participation than wealth or federal structures, challenging assumptions that affluence alone drives engagement. The diffusion analysis indicates that early adopters acted as norm entrepreneurs, while later adopters were often influenced by peer pressure and transnational advocacy. In non-aligned contexts, cities relied on horizontal diffusion and city networks to compensate for national inaction. The internalisation assessment reveals uneven progress: some cities have embedded net-zero targets into law, budgets, and institutions, while others remain at a largely symbolic stage. The study applies insights from norm theory to urban climate governance, focusing on how cities move from rhetorical pledges to embedding net-zero commitments in their institutions. The scoring framework developed here offers a practical tool for assessing the depth of internalisation across different contexts. While the analysis concentrates on large metropolitan areas, the framework could also be extended to medium-sized or smaller cities, where resource constraints and governance conditions may shape distinct pathways of norm uptake. Exploring these cases would help test whether the patterns identified here hold more broadly.
Vedoucí práce: Zdeněk Veselý
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor disert. práce]; disertace; dissertations